Waste Management Strategy in Mosquito Control Efforts: Evaluation of the UIN Walisongo Community Service Program in Kebonsari Village - Hidayati, Dinda Mutia; Nabila, Bulan Ayu (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2025)
This article assesses the effectiveness of waste management strategies implemented by the UIN Walisongo Community Service Program (KKN) Posko 14 in Kebonsari Village. Using Public Relations (PR) planning theory and the State of the Art (SOTA) approach, the strategies included participatory communication, workshops, cleanliness competitions, and banner installation. The analysis results showed that there was a buildup of waste and a mosquito population that had a negative impact on public health, with 60% of residents lacking knowledge and 80% not having waste storage facilities. The efforts made succeeded in raising awareness and improving waste management, but the impact was temporary. Evaluation shows that socialization and workshops are effective in increasing knowledge, but are not sufficient for long-term behavioral change. The cleanliness competition stimulated participation but still requires sustainability. The study recommends improving the waste management system, strengthening ongoing awareness, and additional interventions for more effective and sustainable results. KKN Posko 14 activities had a positive impact but require evaluation and adjustment for long-term impact.